Lateralizing Significance of Quantitative Analysis of Head Movements before Secondary Generalization of Seizures of Patients with Temporal Lobe Epilepsy - O'Dwyer, Rebecca; Silva Cunha, Joao P.; Vollmar, Christian; Mauerer, Cordula; Feddersen, Berend; Burgess, Richard C.; Ebner, Alois; Noachtar, Soheyl (Epilepsia (Copenhagen), 2007)
Purpose: To quantitatively evaluate the lateralizing significance of ictal head movements of patients with temporal lobe epilepsy (TLE). Methods: We investigated EEG‐video recorded seizures of patients with TLE, in which the camera position was perpendicular to the head facing the camera in an upright position and bilateral head movement was recorded. Thirty‐eight seizures (31 patients) with head movement in both directions were investigated. Ipsilateral and contralateral head movements were defined according to ictal EEG. Head movements were quantified by selecting the movement of the nose in relation to a defined point on the thorax (25/s) in a defined plane facing the camera. The duration of the head version was determined independently of the camera angle. The angle, duration, and angular speed of the head movements were computed and inter and intrasubject analyses were performed (Wilcoxon rank sum). Results: Ipsilateral movement always preceded contralateral movement. The positive predictive value was 100% for movement in both directions. The duration of contralateral head version was significantly longer than ipsilateral head movement (6.4 ± 4.1 s vs. 3.9 ± 3.1 s, p < 0.001). The angular speed of both movements was similar (15.5 ± 12.1 deg/s vs. 17.3 ± 13.0 deg/s). Conclusion: The quantitative analysis shows the importance of sequence in the seizure's evolution and duration, but not angular speed for correct lateralization of versive head movement. This quantitative method shows the high lateralizing value of ictal lateral head movements in TLE.